NMR Confirmation and HPLC Quantification of Javamide-I and Javamide-II in Green Coffee Extract Products Available in the Market - Jae B. Park (International Journal of Analytical Chemistry)
Javamide-I/javamide-II are phenolic amides found in coffee. Recent reports suggested that they may contain several biological activities related to human health. Therefore, there is emergent interest about their quantities in coffee-related products. Green coffee extract is a powder extract made of unroasted green coffee beans, available as a dietary supplement. However, there is little information about the amounts of javamide-I/javamide-II in green coffee extract products in the market. Therefore, in this paper, javamide-I/javamide-II were extracted from green coffee extract products and their identifications were confirmed by NMR. After that, the amounts of javamide-I/javamide-II were individually quantified from seven different green coffee extract samples using the HPLC method coupled to an electrochemical detector. The HPLC method provided accurate and reliable measurement of javamide-I/javamide-II with excellent peak resolution and low detection limit. In all seven green coffee extract samples, javamide-II was found to be between 0.28 and 2.96 mg/g, but javamide-I was detected in only five samples in the concentration levels of 0.15–0.52 mg/g, suggesting that green coffee extract products contain different amounts of javamide-I/javamide-II. In summary, javamide-I/javamide-II can be found in green coffee extract products sold in the market, but their amounts are likely to be comparatively different in between green coffee extract brands.